Zobozdravstvena vzgoja (zz-v) v mladinskem zobozdravstvu - Premik, Marjan (Obzornik zdravstvene nege, 1977)
The teeth care instruction of children is an imperative in a well organized dental service. It should always be planned and carried out in the most appropriate manner. The above education is a component part of the routine medical examinations and elementary school curricula, which makes it possible far the preventive measures to be not merely learned, but also practiced by children. First, the starting points should be elaborated, which enable the evaluation of the results of teeth care instruction.